SÁNCHEZ GARCÍA, Raúl y C. SPENCER, Dale (edit.) (2013), Fighting Scholars: Habitus and Ethnographies of Martial Arts and Combat Sports, Anthem Press, London y New York - Malcolm, Dominic (Empiria. Revista de metodología de ciencias sociales, 2015)
.